REPOSISI KANINUS RAHANG ATAS AKIBAT TRAUMA (LAPORAN KASUS) - Mochamad Fahlevi Rizal; Heriandi Sutadi (Faculty of Dentistry, Universitas Indonesia, 2015)
Anterior traumatic injury could be caused by many functional disturbances, such as mastication, speech and esthetic. This condition can be repaired by paying attention to the aspects. Reposition can be done with any appliance but if the reposition must focus on the esthetic aspect, it will require special attention. In this case, it shows that fixed and removable appliance with prosthetic function can be used as alternative treatment for children who suffer traumatic injury.